Genetic portrait of polyamine transporters in barley: insights in the regulation of leaf senescence - Stolarska, Ewelina; Tanwar, Umesh Kumar; Guan, Yufeng; Grabsztunowicz, Magda; Arasimowicz-Jelonek, Magdalena; Phanstiel, Otto; Sobieszczuk-Nowicka, Ewa (Frontiers in Plant Science, 2023)
Nitrogen (N) is one of the most expensive nutrients to supply, therefore, improving the efficiency of N use is essential to reduce the cost of commercial fertilization in plant production. Since cells cannot store reduced N as NH3 or NH4+, polyamines (PAs), the low molecular weight aliphatic nitrogenous bases, are important N storage compounds in plants. Manipulating polyamines may provide a method to increase nitrogen remobilization efficiency. Homeostasis of PAs is maintained by intricate multiple feedback mechanisms at the level of biosynthesis, catabolism, efflux, and uptake. The molecular characterization of the PA uptake transporter (PUT) in most crop plants remains largely unknown, and knowledge of polyamine exporters in plants is lacking. Bi-directional amino acid transporters (BATs) have been recently suggested as possible PAs exporters for Arabidopsis and rice, however, detailed characterization of these genes in crops is missing. This report describes the first systematic study to comprehensively analyze PA transporters in barley, specifically the PUT and BAT gene families in barley (Hordeum vulgare, Hv). Here, seven PUTs (HvPUT1-7) and six BATs (HvBAT1-6) genes were identified as PA transporters in the barley genome and the detailed characterization of these HvPUT and HvBAT genes and proteins is provided. Homology modeling of all studied PA transporters provided 3D structures prediction of the proteins of interest with high accuracy. Moreover, molecular docking studies provided insights into the PA-binding pockets of HvPUTs and HvBATs facilitating improved understanding of the mechanisms and interactions involved in HvPUT/HvBAT-mediated transport of PAs. We also examined the physiochemical characteristics of PA transporters and discuss the function of PA transporters in barley development, and how they help barley respond to stress, with a particular emphasis on leaf senescence. Insights gained here could lead to improved barley production via modulation of polyamine homeostasis.